Fertile androgenetic mice generated by targeted epigenetic editing of imprinting control regions - Yanchang Wei; Tao Yue; Yuanyuan Wang; Yan Yang (Proceedings of the National Academy of Sciences, 2025)
Each new mammalian life begins with the fusion of an oocyte and a sperm to produce a fertilized egg containing two sets of genomes, one from the mother and one from the father. Androgenesis, a way for producing offspring solely from male genetic material, is limited in mammals, presumably due to barriers arising from genomic imprinting, an epigenetic mechanism leading to monoallelic gene expression. Here, we report adult mammalian offspring derived from the genetic material of two sperm cells. These mice, which we refer to as androgenetic mice, were produced via targeted DNA methylation editing of seven imprinting control regions (ICRs) through CRISPR-based epigenome engineering. Two sperm cells were injected into an enucleated oocyte to form putatively diploid embryos. Allele-specific epigenetic editing was achieved by injecting guide RNAs with protospacer adjacent motif (PAM) sequences designed to match one allele but not the other. The birth of androgenetic mice that were able to develop to adulthood demonstrates that mammalian androgenesis is achievable by targeted epigenetic remodeling of a few defined ICRs.